EFEKTIVITAS REBOISASI TERHADAP KUALITAS AIR SUNGAI SIAK DI DESA MAREDAN KECAMATAN TUALANG - Tengku Muhammad Ulul Azmi; Yossi Oktorini; Defri Yoza (Fakultas Pertanian, Universitas Riau, 2018)
This study aims to knowing the physical and chemical parameters in Siak river water the Maredan Village Tualang District, and see the effect of upstream and downstream controls, in this case control Hulu Okura Village and control Downstream Ex PT Perawang Perkasa Industri. The methodology research that used was purposive sampling method. The data analysis used literature study based on the data from Rona Environmental Research Institute of the University of Riau, and compared with the latest data obtained by the researchers. The results of the study showed that water quality of Siak river tend to be preserve after reforestation.